O estatuto teórico do mal-estar em Freud - Túlio Fonseca Coimbra (2019)
It’s a question of investigating the theoretical status of malaise (Unbehagen) in Freud's work. Often quoted and paraphrased, after Freud the notion of malaise was entirely assimilated by culture. Its rampant and trivialized use makes one think that the notion itself would lack definitions and conceptualizations. However, the close study of Freud's work makes it clear that the notion of malaise, especially that used in "Malaise in Civilization", has a specific use, which can be perceived even by the evolution of Freud's thought, which allows us to place it in the constellation of psychoanalytic concepts. However, for this, it must be seen that the concept in psychoanalysis has a specific mark. In the first chapter, we will look at the particularities and idiosyncrasies that the concept assumes in psychoanalysis. Clearly, we seek to address the specific form of psychoanalytic conceptualization. We will see that the psychoanalytic concept is not intended to fix a reality unequivocally and without contradictions, but to enunciate and delimit the equivocity of reality with which psychoanalysis deals, to delimit this same contradiction inherent to the analytic phenomenon. Finally, armed with this essential aspect of psychoanalytic modes of conceptualization, we will see in the second chapter that Freudian malaise meets the requirements of a psychoanalytic concept. More specifically, it is those concepts that start from the clinic and reach the fulcrum of the social. Freudian malaise is the lens through which we can understand subjectively determined forms of internalization. The point here is to defend the hypothesis that malaise is the ultimate concept of Freud's social theory that allows us to situate not only a diagnosis of the epoch, but the way in which a social configuration – and its complex of norms, values and ideals – predetermine the forms of psychic suffering. In Freud, the basis of a theory of social bond is constituted from the forms of affectation of a subject before the social life in which he is launched.